A Significant Role of Chemistry in Drug Development: A Systematic Journey from Traditional to Modern Approaches with Anti-HIV/AIDS Drugs as Examples - Yadav, Madhu; Srivastava, Ritika; Naaz, Farha; Verma, Rajesh; Singh, Ramendra K. (Current Pharmaceutical Design, 2022)
Background: Traditionally, various plant extracts having interesting biological properties were the main source of new drugs. In the last 30 years, the role of chemistry in combination with new technologies, like various computational techniques in chemistry, has witnessed a major upsurge in drug discovery and targeted drug delivery. Objective: This article provides a succinct overview of recent techniques of chemistry that have a great impact on the drug development process in general and also against HIV/AIDS. It focuses on new methods employed for drug development with an emphasis on in silico studies, including identifying drug targets, especially the proteins associated with specific diseases. Methods: The rational drug development process starts with the identification of a drug target as the first phase, which helps in the computer-assisted design of new drug molecules. Synthetic chemistry has a major impact on the drug development process because it provides new molecules for future study. Natural products based semisynthesis or microwave assisted synthesis is also involved in developing newly designed drug molecules. Further, the role of analytical chemistry involves extraction, fractionation, isolation and characterization of newly synthesized molecules. Results: Chemistry plays a key role in drug discovery and delivery by natural process or with the help of synthetic nanoparticles or nanomedicines. So, nanochemistry is also deeply involved in the development of new drugs and their applications. Conclusion: The previous era of drug discovery was dominated only by chemistry, but the modern approaches involve a comprehensive knowledge of synthetic chemistry, medicinal chemistry, computational chemistry and the concerned biological phenomenon.
Keywords: Anti-HIV